ANXIETY LEVEL OF MALES STUDENT SD PEMBANGUNAN JAYA 2 SIDOARJO DURING ALL THE FUTSAL MATCHES OF SD SE-SIDOARJO. - RIDWAN PAMBUDI, AKBAR (Jurnal Kesehatan Olahraga, 2016)
ANXIETYLEVELOF MALES STUDENTSDPEMBANGUNANJAYA2SIDOARJO DURINGALL THEFUTSAL MATCHES OF SDSE-SIDOARJO. This study examined the relationship between anxiety and performance from mental (cognitive) component, behavior (afektive) component, ability (motoric) and physiological (somatic) component. Anxiety is a condition in which individuals feel weak so do not dare to behave and act rationally. Effect of anxiety is the person will feel fear or loss of confidence. There are three levels of anxiety that anxiety is low, medium and high. The purpose of this research was to determine the level of anxiety of atheles SD Pembangunan Jaya 2 Sidoarjo during the tournament. The result of this study was the males futsal player of SD Pembangunan Jaya 2 Sidoarjo with the number of subject taken is 10 players. This research method using descriptive with data analysis, and the proses of data collection is done by filling out the questionnaire. These study results indicate that there is a rather high level of anxiety of athletes SD Pembangunan Jaya 2 Sidoarjo during the tournament between elementary schools of sidoarjo. The score of anxiety level males futsal player of SD Pembangunan Jaya 2 Sidoarjo when the tournament was 51,4. That scores showed of higher anxiety level of anxiety at the time of the match, Also have higher influence on the performance of athletes. It’s been proven males futsal team SD Pembangunan Jaya 2 Sidoarjo lost in the tournament. Key Words: Futsal, AnxietyLevel, and Performance.